Amerika Birleşik Devletleri’nin NSC-68 Çerçevesinde Uyguladığı Soğuk Savaş Stratejisi ve Türkiye’ye Yansımaları - Serpil GÜDÜL (Gazi Akademik Bakış)
After the Second World War, in order to close the gap in the balance of power in world politics, the Union of Soviet Socialist Republics (USSR) increased its influence in Central and Eastern Europe and partially in the Balkans and developed its nuclear capacity. These developments posed an important threat to the USA. In order to fight with this threat, the report number 68 (NSC-68) was prepared and implemented by the American National Security Council in 1950. In this study, in addition to the analysis of the NSC-68 which was one of the most significiant documents of the Cold War, its Cold War strategy implemented against the USSR and its relations with Turkey are examined accordingly. This report was a guide to the Cold War strategy of the United States of America (USA). The USA focused on nuclear armament and aimed to strengthen the military capacities of its allies within the framework of realistic policy outlined in NSC-68. Thus, it aimed to prevent the USSR's strategy to dominate the world politics. The USA organized its relations with Turkey in line with this report. . The USA entered into military and economic cooperation on many issues by making bilateral agreements with Turkey. This cooperation played a major role in preventing the efforts of the USSR to dominate the World politics by going down to the Mediterranean Sea and hence to warm seas.